1996
DOI: 10.1074/jbc.271.28.16506
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidate Phosphohydrolase Catalyzes the Hydrolysis of Ceramide 1-Phosphate, Lysophosphatidate, and Sphingosine 1-Phosphate

Abstract: A Mg 2؉-independent phosphatidate phosphohydrolase was purified from rat liver plasma membranes in two distinct forms, an anionic protein and a cationic protein. Both forms of the enzyme dephosphorylated phosphatidate, ceramide 1-phosphate, lysophosphatidate, and sphingosine 1-phosphate. When assayed at a constant molar ratio of lipid to Triton X-100 of 1:500, the apparent K m values of the anionic phosphohydrolase for the lipid substrates was 3.5, 1.9, 0.4, and 4.0 M, respectively. The relative catalytic effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
102
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(108 citation statements)
references
References 50 publications
4
102
0
2
Order By: Relevance
“…Although detailed kinetic analysis is needed, it is clear that the substrate specificities of the two PAPs cloned are distinct from each other and that dephosphorylation of sphingosine-1-phosphate by PAP-2a occurs to a negligible extent, if any. In this respect, the properties of PAP-2b are more similar to those of rat liver enzyme (17), which degrades all of these substrates at similar rates.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…Although detailed kinetic analysis is needed, it is clear that the substrate specificities of the two PAPs cloned are distinct from each other and that dephosphorylation of sphingosine-1-phosphate by PAP-2a occurs to a negligible extent, if any. In this respect, the properties of PAP-2b are more similar to those of rat liver enzyme (17), which degrades all of these substrates at similar rates.…”
Section: Resultsmentioning
confidence: 62%
“…Waggoner et al (17) recently reported that the type 2 PAP purified from rat liver dephosphorylates lyso-PA, ceramide-1-phosphate, and sphingosine-1-phosphate in addition to PA. Furthermore, the same enzyme preparation was described as capable of dephosphorylating DG pyrophosphate (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…LPA is rapidly dephosphorylated by a family of integral membrane proteins known as lipid phosphate phosphatases (LPPs) [16-18]. The LPP family (also known as PAP2) comprises four members (LPP 1 , LPP 2 , LPP 3 and a splice variant LPP 1a ) which dephosphorylate their lipid substrates, namely LPA, PA, sphingosine 1-phosphate (S1P), and ceramide 1-phosphate [19-21]. All the LPP subtypes are expressed in the brain [18,19,22] but very little is known about their functional roles.…”
Section: Introductionmentioning
confidence: 99%